STUDI LITERATUR: INVESTIGASI KEBUTUHAN DAN URGENSI PENGGUNAAN HRIS PADA UMKM DAN STARTUP DI INDONESIA - Iklima Farhani (Applied Business and Administration Journal, 2022)
Background: Today, both large-scale businesses as well as SMEs and startups are required to utilize technology as optimally as possible to increase operational effectiveness and support marketing. One form of using technology in business operations is the use of management information systems. Human resource Information System (HRIS) is one of the most widely used management information systems. HRIS is very helpful in simplifying employee management which is quite complicated if done manually and in the end is expected to increase company productivity. Objective: Therefore, this literatur aims to determine whether the use of HRIS in SMEs and startups is really necessary or not.Method: The research method used is a literature study approach that summarized articles obtained from Google Scholar, Research Gate, trusted official online news channels, and other search engines using the keywords "HRIS", "HRIS Pros and Cons", "SMEs”, and “Startups”. Result: Human resource Information System (HRIS) provides many benefits for the company its users. However, it cannot be concluded in aggregate whether SMEs and startups need to use HRIS or not. To determine this, it is necessary to analyze and calculate the conditions behind each SME and startup.Conclusion: The use of HRIS in SMEs and Startups needs to consider many things related to the condition of the company itself. This use may or may not be necessary.